1988
DOI: 10.1111/j.1445-5994.1988.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in Patients With Abdominal Pain Syndromes

Abstract: Circadian rhythms for cortisol, 6-sulphatoxy melatonin and core body temperature were compared in control subjects and patients with functional abdominal pain. There were 20 patients with biliary pain after cholecystectomy, ten with biliary pain without cholecystectomy and 14 with irritable bowel syndrome. Rhythms were determined by urine collections at intervals of 4 h for 48 h and by overnight monitoring of core body temperature using the Vitalog system. Data were fitted to a sine curve to yield the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Of note is that those rats with an incorrect cannula placement did not show improvement in either immobility score or mechanical allodynia, suggesting a selective effect of melatonin within ACC. This behavioral data is also consistent with a low plasma melatonin level in WKY rats and in patients suffering from abdominal pain, idiopathic pain, neuropathic pain, or cluster headache (Waldenlind et al, 1987;Almay et al, 1987;Roberts-Thompson et al, 1988;von Knorring, Ekselius, 1994;Leone et al, 1995). It should be noted that the role of a specific MT receptor subtype was not examined in this study, because luzindole (MT2 > MT1) is not a highly selective antagonist for an MT receptor subtype.…”
Section: Discussionsupporting
confidence: 61%
“…Of note is that those rats with an incorrect cannula placement did not show improvement in either immobility score or mechanical allodynia, suggesting a selective effect of melatonin within ACC. This behavioral data is also consistent with a low plasma melatonin level in WKY rats and in patients suffering from abdominal pain, idiopathic pain, neuropathic pain, or cluster headache (Waldenlind et al, 1987;Almay et al, 1987;Roberts-Thompson et al, 1988;von Knorring, Ekselius, 1994;Leone et al, 1995). It should be noted that the role of a specific MT receptor subtype was not examined in this study, because luzindole (MT2 > MT1) is not a highly selective antagonist for an MT receptor subtype.…”
Section: Discussionsupporting
confidence: 61%
“…16 Melatonin may also be involved in mediating gut visceral sensation because patients with functional abdominal pain are reported to have lower urinary excretion of 6-sulphatoxy melatonin and to exhibit a circadian rhythm of lower amplitude compared with healthy controls. 17 In view of the high prevalence of sleep disturbance in IBS patients, and the possible double effects of melatonin in regulating sleep pattern and bowel function, we hypothesised that melatonin may be useful in the treatment of IBS, and its therapeutic effects might be most evident if it was used in IBS patients who suffer from concomitant sleep disturbance. The present study, therefore, aimed to assess the efficacy of exogenous melatonin given at bedtime in relieving IBS bowel symptoms, and in improving rectal sensitivity.…”
mentioning
confidence: 99%
“…23 Melatonin may also play a role in modulating gut visceral sensation because patients with functional abdominal pain disorders have been reported to have reduced urinary excretion of 6-sulphatoxy melatonin and a lower amplitude circadian rhythm compared to healthy controls. 24 Previous studies on adult patients with IBS or FD showed that exogenous melatonin given at bedtime for 2-12 weeks was effective in fully or partially relieving abdominal pain. [13][14][15][16] To date, melatonin did not reduce abdominal pain in children with FD in the only paediatric study available.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism through which melatonin modulates gastrointestinal motility is unclear, although some studies suggest that it may be related to the inhibition of nicotinic channels by melatonin 22 and/or the interplay between melatonin and Ca 2+ ‐activated K + channels 23 . Melatonin may also play a role in modulating gut visceral sensation because patients with functional abdominal pain disorders have been reported to have reduced urinary excretion of 6‐sulphatoxy melatonin and a lower amplitude circadian rhythm compared to healthy controls 24 . Previous studies on adult patients with IBS or FD showed that exogenous melatonin given at bedtime for 2–12 weeks was effective in fully or partially relieving abdominal pain 13–16 .…”
Section: Discussionmentioning
confidence: 99%